NUMERICAL DISCRETIZATION OF STOCHASTIC OSCILLATORS WITH GENERALIZED NUMERICAL INTEGRATORS - Sirma, Ali; Kosker, Resat; Akat, Muzaffer (VINCA INST NUCLEAR SCI, 2021)
In this study, we propose a numerical scheme for stochastic oscillators with additive noise obtained by the method of variation of constants formula using generalized numerical integrators. For both of the displacement and the velocity components, we show that the scheme has an order of 3/2 in one step convergence and a first older in overall convergence. Theoretical statements are supported by numerical experiments.
Keywords: stochastic oscillators; numerical schemes; difference schemes; stochastic trigonemetric integrators; Thermodynamics